Validación de dos herramientas para la evaluación de cambios en las actitudes de alumnos en situaciones frecuentes en cuidado paliativo - Krikorian, Alicia; Román-Calderón, Juan Pablo; Wenk, Roberto; Monti, Carolina (Psicooncología, 2016)
Objective: To determine the psychometric properties of two scales designed to examine attitudes regarding palliative care: Comfort Scale in Palliative Care (CSPC, Pereira et al.) and Tanatophobia Scale (TS, Merrill et al.)Method: Seventy-seven students who completed an online course on psychosocial aspects of palliative care offered by the Latin American Association of Palliative Care participated in the study. They also completed the scales before and after the course. Construct validity and reliability of the CSPC and the TS were assessed using a Principal Components Analysis, internal reliability coefficient and test-retest reliability. Further, comparative statistics between the pre-course and post-course results were obtained in order to determine changes in attitudes.Results: The Principal Components Analysis showed satisfactory fit to the data. 3 components were extracted: two for the CSPC and one for the TS, which explained 55.37% of the variance. Internal consistency coefficients were satisfactory in all cases and Cronbach´s Alphas were satisfactory for all the scales, particularly for the CSPC. Test-retest reliability in t1 and t2 was found to be non significant, indicating that measures were not related in time. Regarding pre-course/post-course comparisons, significant changes in comfort assisting patients (p = 0.004) and comfort assisting families (p = 0.001) following the course were identified, but changes in thanatophobia were non significant (p > 0.05).Conclusions: both scales are valid and reliable. Attitudes regarding the practice of palliative care and how they change, particularly regarding psychosocial issues, can be accurately measured using the examined scales.
Keywords: Education; palliative care; assessment tools; validation.